2016
DOI: 10.1371/journal.pone.0151901
|View full text |Cite
|
Sign up to set email alerts
|

Association between SIRT1 Gene Polymorphisms and Breast Cancer in Egyptians

Abstract: BackgroundBreast cancer is reported to cause the highest mortality among female cancer patients. Previous studies have explored the association of silent mating-type information regulator 2 homolog 1 (SIRT1) gene expression with prognosis in breast cancer. However, no studies exist, so far, on the role of SIRT1 gene polymorphism in breast cancer risk or prognosis. The present study aimed to assess the association between SIRT1 gene polymorphisms and breast cancer in Egyptians.MethodsThe study comprised 980 Egy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
35
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 49 publications
1
35
1
1
Order By: Relevance
“…Even though the laboratory techniques for the investigation of SIRT-1 expression are not uniform and there is lack of research in this area, the data found in the Erechim-RS research are consistent with the information in the literature that suggests that the change in SIRT-1 expression is associated with breast cancer [32].…”
supporting
confidence: 78%
See 2 more Smart Citations
“…Even though the laboratory techniques for the investigation of SIRT-1 expression are not uniform and there is lack of research in this area, the data found in the Erechim-RS research are consistent with the information in the literature that suggests that the change in SIRT-1 expression is associated with breast cancer [32].…”
supporting
confidence: 78%
“…Epigenetic changes, including histone modifications, are critical for mammary carcinogenesis, but the association of expression of SIRT1 with the clinical features and prognosis of breast cancer have not yet been clarified [32]. Changes in the level of expression of sirtuin-1 (SIRT-1) and other molecules related to the signaling pathways of tumor cells have been investigated in many types of tumors, including breast cancer, but the association degree these expressions with the clinical prognosis of patients have not been definitively determined [25,33,34].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This study shows that the rs3758391 associated with T2D, breast cancer, autoimmune thyroid disease, lupus erythematosus, and depression disorders, among others (Consiglio et al., ; Hathaway et al., ; Kovanen, Donner, & Partonen, ; Rizk et al., ; Sarumaru et al., ) and the rs1800470 associated with T2D, diabetic nephropathy, acute coronary syndrome, and asthma (Dragicevic, Petrovic‐Stanojevic, & Nikolic, ; Fragoso et al., ; Raina et al., ; Yang et al., ) are correlated with gene expression levels of SIRT1 and TGF‐β1 , respectively, in peripheral blood from adults. However, rs3758391, rs932658 (in LD with rs3758391), and rs1800470 are not located in DNA‐protein binding sites in the cell line BxPC‐3.…”
Section: Resultsmentioning
confidence: 72%
“…However, research has been performed on the association of SIRT1 polymorphisms and risk of other cancers. A recent study of Egyptian women found a positive association between SIRT1 rs12778366 TT genotype and the risk of breast cancer as compared to TC and CC genotypes, and carrying the rs12778366 TT genotype was associated with higher serum SIRT1 levels compared to TC and CC genotypes in breast cancer cases but not controls, while, overall, breast cancer cases had significantly higher serum SIRT1 levels than controls 42 . A study of pituitary adenoma patients found that the CC SIRT1 rs12778366 genotype was more common in patients compared to healthy controls, while the TC genotype was rarer in patients and no difference between the groups was found when considering the TT genotype 43 .…”
Section: Discussionmentioning
confidence: 95%